Discovery of strongly variable X-ray polarization in the neutron star low-mass X-ray binary transient XTE J1701-462 - Cocchi Massimo; Gnarini Andrea; Fabiani Sergio; Ursini Francesco; Poutanen Juri; Capitanio Fiamma; Bobrikova Anna; Farinelli Ruben; Paizis Adamantia; Sidoli Lara; Veledina Alexandra; Bianchi Stefano; et al. (EDP SCIENCES S A, 2025)
Context. After about 16 years since its first outburst, the transient neutron star low-mass X-ray binary XTE J1701-462 turned on again in September 2022, allowing for the first study of its X-ray polarimetric characteristics by a dedicated observing program with the Imaging X-ray Polarimeter Explorer (IXPE).Aims. Polarimetric studies of XTE J1701-462 have been expected to improve our understanding of accreting weakly magnetized neutron stars, in particular, the physics and the geometry of the hot inner regions close to the compact object.Methods. The IXPE data of two triggered observations were analyzed using time-resolved spectroscopic and polarimetric techniques, following the source along its Z-track of the color-color diagram.Results. During the first pointing on 2022 September 29, an average 2-8 keV polarization degree of (4.6 +/- 0.4)% was measured, the highest value found up to now for this class of sources. Conversely, only a similar to 0.6% average degree was obtained during the second pointing ten days later.Conclusions. The polarimetric signal appears to be strictly related to the higher energy blackbody component associated with the boundary layer (BL) emission and its reflection from the inner accretion disk, and it is as strong as 6.1% and 1.2% (> 95% significant) above 3-4 keV for the two measurements, respectively. The variable polarimetric signal is apparently related to the spectral characteristics of XTE J1701-462, which is the strongest when the source was in the horizontal branch of its Z-track and the weakest in the normal branch. These IXPE results provide new important observational constraints on the physical models and geometry of the Z-sources. Here, we discuss the possible reasons for the presence of strong and variable polarization among these sources.